Do tumor-infiltrating lymphocytes really indicate favorable prognosis in epithelial ovarian cancer?. (August 2017) - Yildirim, Nuri; Akman, Levent; Acar, Kamuran; Demir, Sibel; Ozkan, Sultan; Alan, Nuran; Zekioglu, Osman; Terek, M. Cosan; Ozdemir, Necmettin; Ozsaran, Aydin
Abstract: Objective: The aim of this study is to evaluate the impact of lymphocyte infiltration on prognostic parameters, recurrence and survival in ovarian cancer. Study design: Sixty-two patients who were primarily operated for epithelial ovarian carcinoma between 1997 and 2008 were included. CD3, CD4, CD8, CD20 and FoxP3 expressions were evaluated immunohistochemically on sections obtained from paraffin-embedded tissues. Results: Median follow up was 87 months. In whole cohort, CD3+ and CD8+ T lymphocyte infiltrations were significantly higher in patients with high-grade tumors, advanced stage tumors and the patients with omental metastasis (for CD3 p = 0.0001, p = 0.029, p = 0.016; for CD8 p = 0.044, p = 0.002, p = 0.046, respectively). DFS was significantly lower among patients with CD8+ T lymphocytes with regard to patients who did not have CD8+ T lymphocyte infiltration (p = 0.028). In univariate analysis, presence of CD8 cytotoxic T lymphocyte infiltration (p = 0.03), stage (0.0001), tumor grade (p = 0.007), omental metastasis (p = 0.0001) and lymph node metastasis (p = 0.0001) were significant risk factors for recurrence. But in multivariate analysis, only stage [HR: 116.6 (95% CI: 13.09-1039.45) (p = 0.0001)] was found as an independent risk factor for recurrence. Conclusion: CD3+ and CD8+ T lymphocyte infiltrations were related with advanced stage, high-grade tumor and the omental metastasis in ovarian cancer. DFS was significantly shorter in patients with CD8+ T lymphocyte infiltration. CD3+ and CD8+ T lymphocyte infiltrations were related with poor prognosis in ovarian cancer.